2007
DOI: 10.3390/s7071123
|View full text |Cite
|
Sign up to set email alerts
|

Indium Tin Oxide-Polyaniline Biosensor: Fabrication and Characterization

Abstract: Abstract:In this study, a novel indium tin oxide (ITO)-polyaniline (Pani) biosensor was designed, fabricated, and characterized. Initial testing was conducted for the detection of bovine viral diarrhea virus (BVDV). The biosensor design was based upon the specific nature of antibodies to capture the target virus, and the conductive properties of self-doped Pani to translate the antibody-antigen binding into a quantifying signal. The first part of the study was to assess the feasibility of the self-doped Pani t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…allows increasing the hydrophilicity of surfaces. 19 The physical properties of the exfoliated nanosheets were characterised via a range of techniques including Raman, UV-vis, photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), and ultraviolet photoelectron spectroscopy (UPS). The morphological and structural properties of the nanosheets were also investigated using atomic force microscopy (AFM) and high-resolution transmission electron microscopy (HR-TEM).…”
Section: Introductionmentioning
confidence: 99%
“…allows increasing the hydrophilicity of surfaces. 19 The physical properties of the exfoliated nanosheets were characterised via a range of techniques including Raman, UV-vis, photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), and ultraviolet photoelectron spectroscopy (UPS). The morphological and structural properties of the nanosheets were also investigated using atomic force microscopy (AFM) and high-resolution transmission electron microscopy (HR-TEM).…”
Section: Introductionmentioning
confidence: 99%
“…All of these methods have their own merits and demerits. Hence, many studies have been carried out to increase their individual merits [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Constant potential amperometry (0.5 V), where a constant potential is applied and the current is measured, was used and the current values were recorded at fixed time intervals over 15 minutes. Previous studies have demonstrated that a potential of 0.2 V to 0.8 V is a preferable input signal when dealing with whole cells or other biological elements [24][25][26][27]. Based on this information, the potential of 0.5 V was arbitrarily selected.…”
Section: Resistance Measurements and Electrical Theorymentioning
confidence: 99%